Enhancing China’s Regulatory Framework for Eco-Industrial Parks : Comparative Analysis of Chinese and International Green Standards - World Bank (World Bank, Washington, DC, 2019)
China has impressed the world with its rapid economic growth over the past four decades, during which time it has increased its real income per capita by more than 25 times. However, the attendant environmental costs have also been significant, jeopardizing economic and social gains from growth. To move toward sustainable development and reduce the environmental impact of further economic growth, the Chinese government has started to prioritize green development and the building of an ecological civilization. China’s 13th Five-Year Plan (2016−2020) has upgraded the building of the ecological civilization to the level of national strategy — a policy target of top priority.According to the Ministry of Ecology and Environment (MEE), industrial parks (IPs) are the key source of industrial production and all new industrial projects are required to be operated within industrial parks (Zhang 2018). The growing concentration of industrial activities within IPs suggests that an increasing proportion of industrial pollution will be produced in IPs. Thus, promoting green development of IPs will be vital for the achievement of China’s and the world’s sustainable development goals.Effective management of IPs toward green development requires a well-functioning regulatory framework to provide standards, requirements, guidelines, and robust monitoring and evaluation (M&E) frameworks. Although China does not have a specific IP management law, a comprehensive regulatory framework is in place, covering different legislative levels including (from top to bottom in terms of their importance) laws, regulations, national policies, and standards and indicators. This regulatory framework covers multiple aspects of IP management, including requirements concerning the economic and environmental performances of IPs.This report conducts a comparative analysis between the Chinese green standards and the EIP Framework across all four dimensions—park management and economic, social, and environmental performance— to identify differences and share policy recommendations for further improvements of the Chinese standards.